2016
DOI: 10.1186/s12889-016-3776-4
|View full text |Cite
|
Sign up to set email alerts
|

Modifying effects of education on the association between lifestyle behaviors and the risk of obesity: evidence from South Korea

Abstract: BackgroundNo previous study has explored the interactions between education and lifestyle in relation to obesity. This study hypothesized that education may be obesogenic through its interplay with lifestyle behaviors.MethodsData for a nationally representative sample (6937 men and 9333 women) from the Korea National Health and Nutrition Examination Survey (2010–2012) were analyzed. Multivariate logistic regressions were performed for three education levels and six lifestyle behaviors, each of which comprised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…High education may have positive effect on reducing number of having lifestyle risk factors [27,28]. Subjects educated above high school have lower possibility of having three or four risk factors than subjects with primary of middle school education.…”
Section: Discussionmentioning
confidence: 99%
“…High education may have positive effect on reducing number of having lifestyle risk factors [27,28]. Subjects educated above high school have lower possibility of having three or four risk factors than subjects with primary of middle school education.…”
Section: Discussionmentioning
confidence: 99%
“…36 In South Korea and China, women with lower educational attainment are more likely to have obesity compared to women with higher educational attainment, though the opposite is true for men. 37,38 Stage 3 of the obesity transition is primarily characterised by a closing of the gender gap, and a reversal of the socioeconomic differences due to an acceleration of obesity among previously lower-BMI sub-populations in Stage 2 (as opposed to declines in the prevalence of obesity in any sub-population). The prevalence among children continues to increase, although the patterns by gender and socioeconomic status are more mixed than for adults.…”
Section: Stages Of the Obesity Transitionmentioning
confidence: 99%
“…However, no study has performed a multi-dimensional analysis of the associations between these variables and education level in relation to obesity, except one recent study that dealt with the associations between lifestyle behaviours and education level relation to obesity [105]. This study considered a total of six lifestyle behaviours-smoking status, the risk from drinking alcohol, physical exercise activity, daily sleep duration, daily energy intake, and level of stress-and reported that the modifying effects of education level on the associations between lifestyle behaviours and obesity depend on both sex and lifestyle behaviour [105]. Similar to this study, future studies need to elucidate how a person's characteristics influence, either as a confounder or an effect modifier, the association between a person's education level and risk of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, for expository convenience, this study precluded the interactions between education level and other covariates. Some recent studies found that education plays a role as either a confounder or modifier in the associations between other socioeconomic status indicators (or health lifestyles) and obesity risk [105,107]. Fifth, because of the small number of participants with college or higher level of education in older people, particularly for women, the CIs of the predicted probability of obesity in participants with college or higher level of education tended to widen as they got older.…”
Section: Limitationsmentioning
confidence: 99%